Myocardial bridging and endothelial dysfunction – Computational fluid dynamics study. (6th March 2019) - Javadzadegan, Ashkan; Moshfegh, Abouzar; Qian, Yi; Kritharides, Leonard; Yong, Andy S.C.
Abstract: Myocardial bridging (MB) is associated with endothelial dysfunction in patients with angina and non-obstructive coronary artery disease. This study aims to determine if there is a link between abnormal blood flow patterns and endothelial dysfunction in patients with MB. Ten patients with MB in their left anterior descending (LAD) artery were selected, 5 of whom had endothelial dysfunction and 5 had no endothelial dysfunction based on their response to acetylcholine. Similarly, 10 patients without MB in their LAD, 5 of whom had endothelial dysfunction and 5 of whom had no endothelial dysfunction, were studied as a control group. Transient computational fluid dynamics simulations were performed to derive wall shear stress (WSS) over the entire vessel including proximal, middle and distal segments. Patients with MB and endothelial dysfunction had lower WSS in the proximal LAD and greater WSS in the mid-LAD than patients with MB but without endothelial dysfunction. When comparing patients with endothelial dysfunction, those with MB had significantly lower shear stress in the proximal LAD (0.32 ± 0.14 Pa (with MB) vs 0.71 ± 0.38 Pa (without MB), p = 0.01) and greater shear stress in the mid-LAD (2.81 ± 1.20 Pa (with MB) vs 1.66 ± 0.31 Pa (without MB), p = 0.014) than patients without MB. Our findings demonstrated that the presence of MB significantly contributes to low WSS and endothelial dysfunction relationship.